Study of Multiband DRA for Mobile communication - Yadav, Dorik Narayan (Himalayan Physics, 2015)
The explosive demand for mobile communication and information transfer using personal devices such as mobile phone or notebook computer has caused the need for major advancements of antenna design. With the development of 3G and 4G technologies multiband and wideband antennas operating at additional frequency band such as UMTS and LTE are required. In this chapter it is initially presented the fundamental parameters of antenna to be taken into account while designing an antenna and determining the operating frequency bands. Multiband antennas which are used especially in mobile unit are described. The techniques to make an antenna convenient for multiband operations are given. There different antennas such as monopoles, PIFA are examined with several examples in the literatures. In the last part, the types of wideband antennas (micros strip patch antenna, DRA of planer) used in mobile communication which are more appropriate for base station or access point applications are presented. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 75-77